2021
DOI: 10.3390/agronomy11020307
|View full text |Cite
|
Sign up to set email alerts
|

Quanti-Qualitative Response of Swiss Chard (Beta vulgaris L. var. cycla) to Soil Amendment with Biochar-Compost Mixtures

Abstract: In recent years, soil addition with organic amendments, such as biochar and compost, has gained attention as an effective agronomic practice to sustain soil fertility, enhance plant growth and crop yield. Well known are the positive effects of compost on yield of a wide crop varieties, while both positive and negative responses are reported for biochar Therefore, the aim of the study was to verify the effect of biochar mixed with three types of compost on quanti-qualitative response of Swiss chard (Beta vulgar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
(71 reference statements)
5
10
0
Order By: Relevance
“…e obtained results were in agreement with those of Sacan and Yanardag [25], Colonna et al [26], and Mzoughi et al [4]. e differences in chemical compositions are related to the soil composition and the use of organic amendments [27].…”
Section: Resultssupporting
confidence: 90%
“…e obtained results were in agreement with those of Sacan and Yanardag [25], Colonna et al [26], and Mzoughi et al [4]. e differences in chemical compositions are related to the soil composition and the use of organic amendments [27].…”
Section: Resultssupporting
confidence: 90%
“…Comparatively, most of these studies evaluated the content in chard, especially commercial samples. The content of nitrate observed in these studies varied from very low (<200 mg/kg) and low (200-500 mg/kg) to extremely high (>5000 mg/kg) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Only the study carried out by Menal-Puey and Asensio [29] reported values in the range of medium (500-1000 mg/kg) and extremely high.…”
Section: Nitrate Content In Beta Vulgaris Varietiesmentioning
confidence: 99%
“…Focusing on Swiss chard, several studies have reported the positive, negative or neutral effects of different organic amendment types and doses on the quantitative–qualitative response of this crop [ 41 , 42 , 43 , 44 ]. In previous experiments, where soil was treated with biochar and different compost types, used alone [ 45 ] or in mixture [ 46 ], we found that vermicompost and compost, respectively deriving from cattle manure and cattle anaerobic digestate, improved the growth of Swiss chard compared to compost deriving from olive pomace and biochar obtained from vine pruning residues. Furthermore, a following experiment [ 47 ], which evaluated the co-application of a biochar from wood chips and a biochar from vine prunings, respectively, with vermicompost from cattle manure (as organic fertilizer) or ammonium nitrate (as chemical fertilizer), showed again the significant effect of vermicompost on both the number and fresh weight of leaves in all five harvests performed during the growth cycle; this effect was similar to that of ammonium nitrate.…”
Section: Introductionmentioning
confidence: 96%